(untitled) (Per Musi, 2021)
The study of musical signification constitutes an important key for the comprehension of Shostakovich’s music. This becomes particularly evident when one observes that social and political background plays an important role in his compositional process through the configuration of specific musical topics on structural positions of his music. These specific topics have arisen after cultural and social events during the establishment of the Soviet Union and became typical elements of the Soviet Music. This paper aims to show the function of these elements as compositional roots in the creative concept of Shostakovich’s music. The rising of the concept of musical topic after Leonard Ratner (1980) has opened new paths for a consistent comprehension of the musical discourse, identifying social and cultural signs that may articulate ideas which go beyond the music itself: ideology, criticism and politics became elements of musical expression, composing a new soundscape of music in Revolutionary Russia.